Microstructural Evolution in 42SiCr Steel in a High-Temperature Chamber Under Microscope Objective - Pekovic, Michal; Jirkova, Hana; Rubesova, Katerina; Janda, Tomas; Bures, Radovan (Manufacturing Technology Journal, 2020)
Thanks to today's computer programs, engineers can derive a large amount of information from chemical com-position of a material. This information includes phase transformation temperatures Ac1, Ac3, Ms and Mf. CCT and TTT diagrams for austenite decomposition can be determined as well. When steel is heated, austenite grains nu-cleate and grow in the initial microstructure. On cooling, the grains decompose into pearlite, ferrite, cementite and hardening phases. Transformations of this kind are thoroughly described in literature: the ways the individual phases form and the speed of their formation and temperatures involved. However, in-situ visual recordings of such transformations are relatively rare. With Linkam TS1400XY high-temperature stage and chamber integrat-ed in an optical microscope, one can observe phase transformations in situ during heating and cooling. This paper explores microstructural evolution in 42SiCr steel in the course of heat treatment in a high-temperature chamber on an optical microscope stage which offers observation of changes in the material right under the microscope objective.
Keywords: high-temperature chamber; phase transformations; optical and electron microscopy; heat treatment